Carbon sequestration dynamic, trend and efficiency as affected by 22‐year fertilization under a rice–wheat cropping system. Issue 5 (9th August 2016) - Zhao, Yanan; Zhang, Yueqiang; Liu, Xueqin; He, Xinhua; Shi, Xiaojun
Abstract: The maintenance and accumulation of soil organic carbon (SOC) in agricultural systems is critical to food security and climate change, but information about the dynamic trend and efficiency of SOC sequestration is still limited, particularly under long‐term fertilizations. In a typical Purpli‐Udic Cambosols soil under subtropical monsoon climate in southwestern China this study thus estimated the dynamic, trend and efficiency of SOC sequestration after 22‐year (1991–2013) long‐term inorganic and/or organic fertilizations. Nine fertilizations under a rice–wheat system were examined: control (no fertilization), N, NP, NK, PK, NPK, NPKM (NPK plus manure), NPKS (NPK plus straw), and 1.5NPKS (150% NPK plus straw). Averagely, after 22‐years SOC contents were significantly increased by 4.2–25.3% and 10.2–32.5% under these fertilizations than under control conditions with the greatest increase under NPKS. The simulation of SOC dynamic change with an exponential growth equation to maximum over the whole fertilization period predicted the SOC level in a steady state as 18.1 g kg −1 for NPKS, 17.4 g kg −1 for 1.5NPKS, and 14.5–14.9 g kg −1 for NK, NP, NPK, and NPKM, respectively. Either inorganic, organic or their combined fertilization significantly increased crop productivity and C inputs that were incorporated into soil ranging from 0.91 to 4.63 t (ha · y) −1 . The C sequestration efficiency was lower under NPKM, NPKS, and 1.5NPKS (13.2%, 9.0%, and 10.1%) than under NP and NPK (17.0% and 14.4%). The increase of SOC was asymptotical to a maximum with increasing C inputs that were variedly enhanced by different fertilizations, indicating an existence of SOC saturation and a declined marginal efficiency of SOC sequestration. Taken all these results together, the combined NPK plus straw return is a suitable fertilizer management strategy to simultaneously achieve high crop productivity and soil C sequestration potential particularly in crop rotation systems.